DEVELOPMENT OF CHARACTER EDUCATION MODELS - Ike Nilawati Rohaenah; Sahudi; Aan Hasanah (Departement Of Master Of Islamic Education Graduate Programme Sultan Muhammad Syafiuddin Institute Of Islamic Studies Sambas, Indonesia, 2021)
The research method used was qualitative. The research site of Mutiara Bangsa Health Vocational School, Purwakarta, West Java. The number of respondents was 38 grade X students. The results of the study were as follows: 1) The character education curriculum at Mutiara Bangsa Health Vocational School was arranged perfectly. 70% of the subject matter is in the form of practice and 30% is theory. 2). The character education model has been used by using the